Preliminary findings of potentially resistant goosegrass (Eleusine indica) to glufosinate-ammonium in Malaysia - Jalaludin, Adam; Ngim, Jeremy; Bakar, Baki; Alias, Zazali (Wiley, 2010)
Goosegrass (Eleusine indica), regarded as one of the world's worst weeds, is highly pernicious to cash crop-growers in Malaysia. Following reports in 2009 that glufosinate-ammonium failed to adequately control goosegrass populations in Kesang, Malacca, and Jerantut, Pahang, Malaysia, on-site field trials were conducted to assess the efficacy of glufosinate-ammonium towards goosegrass in both places. Preliminary screenings with glufosinate-ammonium at the recommended rate of 495 g ai ha-1 provided 82% control of the weed at a vegetable farm in Kesang, while the same rate failed to control goosegrass at an oil palm nursery in Jerantut. The ensuing greenhouse evaluations indicated that the ``Kesang'' biotype exhibited twofold resistance, while the ``Jerantut'' biotype exhibited eightfold resistance towards glufosinate-ammonium, compared to susceptible goosegrass populations. The occurrence of glufosinate resistance in goosegrass calls for more integrated management of the weed to prevent escalating resistance and further proliferation of the weed in Malaysia.